2007
DOI: 10.1002/jhm.176
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting measures of hospital quality: Ratings from “Hospital Compare” versus “Best Hospitals”

Abstract: BACKGROUNDIn April 2005 the Centers for Medicare and Medicaid Services launched “Hospital Compare,” the first government‐sponsored hospital quality scorecard. We compared the ranking of U.S. News and World Report's “Best Hospitals” with Hospital Compare performance ratings.METHODSWe examined Hospital Compare scores for core measures related to care for acute myocardial infarction (AMI), congestive heart failure (CHF), and community‐acquired pneumonia (CAP). We calculated composite scores for the disease‐specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 8 publications
0
33
0
5
Order By: Relevance
“…Halasyamani and Davis, 2007;McGaghie and Thompson, 2001) than others (e.g. Wang, Wang, Lichtman, Bradley, Normand and Krumholz, 2007;Souba, 2008;Philibert, 2009 (2007) found an imperfect correlation for cardiac diagnoses and respiratory disorders between the highest-ranked hospitals in USNWR and those in ‗Hospital Compare'.…”
Section: Discussionmentioning
confidence: 96%
“…Halasyamani and Davis, 2007;McGaghie and Thompson, 2001) than others (e.g. Wang, Wang, Lichtman, Bradley, Normand and Krumholz, 2007;Souba, 2008;Philibert, 2009 (2007) found an imperfect correlation for cardiac diagnoses and respiratory disorders between the highest-ranked hospitals in USNWR and those in ‗Hospital Compare'.…”
Section: Discussionmentioning
confidence: 96%
“…In this issue of the Journal of Hospital Medicine, Halasyamani and Davis report that there is relatively poor correlation between the Hospital Compare scores of the Centers for Medicare and Medicaid Services (CMS) and U.S. News and World Report's "Best Hospitals" rankings. 1 The authors note that this is not necessarily surprising, as the methodologies of these rating systems are quite different, although their purposes are functionally similar.…”
mentioning
confidence: 99%
“…In Halasyamani and Davis's study, only 2.9% of hospitals reported all 14 Hospital Compare core performance measures used in their analysis. 1 Evidence suggests that poor performance is a strong disincentive to voluntarily report quality measures to the public. 5 And because there is no evidence that this type of transparency initiative will drive volume to higher-quality programs, publicly reporting quality measures may not provide a strong enough incentive for hospitals to allocate resources to the improvement of the quality of care they deliver in these specific areas.…”
mentioning
confidence: 99%
“…Some research indicates that being named to U.S. News & World Report's "Best Hospitals" list is associated with lower thirty-day mortality, 4 but other studies have found no association between the U.S. News list and readmissions, 5 wide variation on a number of indicators, 6 and discrepancies with other ratings systems such as the Centers for Medicare and Medicaid Services' (CMS's) Hospital Compare. 7 Hospital rating systems use a variety of methods for distinguishing "high" performers from "low" performers, often creating the paradox of hospitals' simultaneously being considered best and worst depending on the rating system used. [8][9][10] For example, 43 percent of hospitals classified as having below-average mortality by one risk-adjustment method were classified as having above-average mortality by another method.…”
mentioning
confidence: 99%